Bigot de Morogues—Governor on the Move - Kraszewski, Igor (Sensus Historiae, 2024)
Paul Bigot was the tutor to the sons of a number of important aristocratic families in Central Europe (Silesia, Poland, Courland, Russia) at the end of the eighteenth century. His position vacillated between servant and friend of the house, and his relationship with his employers varied, but he was always dependent on them for his movements and upkeep. Not entirely free in his movements, he travelled in search of new posts, to educate himself or to accompany the families of his master-employers. Paul Bigot took a keen interest in cultural life, particularly music, theatre, literature and also natural philosophy, geography, languages and curiosities. We know about his interests and itineraries thanks to the detailed diary that has come down to us in several volumes (with some gaps) and which is the subject of the research project planned to result in a critical edition. Thanks to this important corpus, we can determine both the character of a preceptor’s travels at the end of the 18th century and the limits of his freedom of movement and intellectual freedom.